TESTING OF WEB-BASED LEARNING MEDIA INFORMATION SYSTEMS WITH WHITE BOX AND BLACK BOX TESTING - Muhammad Luthfi Hamzah; Viki Kurniawan; Suryani Suryani; Septi Kenia Pita Loka; Yulia Ikhsani; Siti Badriah (Lembaga Riset dan Inovasi Almatani, 2025)
Learning media is a tool in the process of delivering learning materials to students both inside and outside the classroom. Current technological developments have also brought developments in learning media. The most widely used learning media today is website-based information systems. Testing is a stage in the software development life cycle. Testing is conducted to determine the feasibility and quality of the information system. Based on this, this study aims to test a website-based learning information system using white box and black box methods based on equivalence partitions. Testing was conducted on four features: login, material input, attendance, and logout. Based on the testing conducted on these four features, the results indicate that the features are functioning as expected.